Ca2+ binding to F‐ATP synthase β subunit triggers the mitochondrial permeability transition. (15th May 2017) - Giorgio, Valentina; Burchell, Victoria; Schiavone, Marco; Bassot, Claudio; Minervini, Giovanni; Petronilli, Valeria; Argenton, Francesco; Forte, Michael; Tosatto, Silvio; Lippe, Giovanna; Bernardi, Paolo
Abstract: F‐ATP synthases convert the electrochemical energy of the H + gradient into the chemical energy of ATP with remarkable efficiency. Mitochondrial F‐ATP synthases can also undergo a Ca 2+ ‐dependent transformation to form channels with properties matching those of the permeability transition pore (PTP), a key player in cell death. The Ca 2+ binding site and the mechanism(s) through which Ca 2+ can transform the energy‐conserving enzyme into a dissipative structure promoting cell death remain unknown. Through in vitro, in vivo and in silico studies we (i) pinpoint the "Ca 2+ ‐trigger site" of the PTP to the catalytic site of the F‐ATP synthase β subunit and (ii) define a conformational change that propagates from the catalytic site through OSCP and the lateral stalk to the inner membrane. T163S mutants of the β subunit, which show a selective decrease in Ca 2+ ‐ATP hydrolysis, confer resistance to Ca 2+ ‐induced, PTP‐dependent death in cells and developing zebrafish embryos. These findings are a major advance in the molecular definition of the transition of F‐ATP synthase to a channel and of its role in cell death. Synopsis: In response to Ca 2+ ions mitochondria can undergo a permeability transition (PT). This study provides evidence that Ca 2+ ‐binding to the catalytic β subunit of F1 F0 ATPase induces a conformational change that is transduced to the OSCP subunit and the lateral stalk to induce pore opening. Onset of the PT depends on Ca 2+ binding to T163 of F‐ATP synthase β subunit, which in physiological catalysis coordinates Mg 2+ . Ca 2+ binding to the catalytic site may induce a conformational change that is transmitted to the peripheral stalk through OSCP, leading to the PT. A T163S mutation increases Mg 2+ ‐ATPase and inhibits Ca 2+ ‐ATPase activity, prevents PT‐dependent HeLa cells death and lowers incidence of apoptosis in developing zebrafish embryos. Abstract : In response to Ca 2+ ions mitochondria can undergo a permeability transition (PT). This study provides evidence that Ca 2+ ‐binding to the catalytic β subunit of F1 F0 ATPase induces a conformational change that triggers pore opening.